Childfree Perspectives Among Urban Muslim Youth in Indonesia : Insight From Feminist and Indonesian Progresive Islam Perspective - Najmi, Renci; Jennifer Nahyu, Kim; Fikri Ramadhan, An-Najmi; Abadi, Mansurni (Al-madinah: Journal of Islamic Civilization, 2025)
This study investigates the childfree decision among urban Muslim youth in Indonesia, focusing on the negotiation between contemporary personal autonomy, patriarchal traditions, and religious expectations. Employing a qualitative methodology centered on discourse analysis, the research utilizes a dual framework of feminist theory and progressive Islamic interpretation. It explores the interaction between feminist ideals of reproductive rights and gender equality and the religious discourses of Indonesia's two largest Islamic organizations, Nahdlatul Ulama (NU) and Muhammadiyah. The findings indicate that NU adopts a conditional, permissible (mubah) stance on childfree choices when justified by health or economic considerations, whereas Muhammadiyah embraces more progressive, modernist perspective that frames the decision as a matter of social responsibility. From a feminist standpoint, the childfree choice is conceptualized as an assertion of autonomy and resistance to the patriarchal "motherhood imperative." The study identifies substantial tensions between the rights-based discourse of feminism and the permission-based reasoning characteristic of progressive Islam. Nevertheless, it also identifies opportunities for alignment through reinterpretive strategies that foreground Islamic principles of public interest (maslahah) and the prohibition of coercion. The research concludes that fostering dialogue between feminist hermeneutics and progressive Islamic thought can promote a more inclusive understanding of family and personal choice, thereby reconciling religious faith with the evolving realities faced by urban Muslim youth in Indonesia.